Peluang dan Tantangan Komersialisasi Biodisel-Review - Mahreni Mahreni (Eksergi, 2010)
Hydrogen is one of the environmentally friendly fuel, however hydrogen is not always available due to continuously increasing energy demand and fossil fuel availability become more limited. Gap between demand and supply is essential to find alternative fuels. Biodiesel could be a substituent for fossil fuels, especially for hydrogen. Biodiesel could be made by mixing vegetable oils or fats with fossil fuel with a ratio of (5-20) wt.% however in a long time effect of this mixture can damage the engine. To overcome the problem, biodiesel can be synthesized via transesterification of oil and alcohol with the aid of acid or base catalyst to produce glycerol and FAME (Fatty Acid Methyl Ester). Challenges faced for the commercialization of biodiesel among others, (1) expensive raw material (edible oil), (2) reaction time and separation of the relatively long time (minimum 15 hours), (3) the use of acid catalysts still leaves the problem of corrosion and corrosion of machine tools and pollution to the environment by the catalyst. To make biodiesel competitive in the market, used oil (waste cooking oils, WCO), agricultural waste, and recent studies using microalgae could be used as source of biodiesel production. To shorten the reaction time, reaction was carried out using ultrasonic reactor technology and to minimize environmental pollution to use the solid catalyst. This paper will summarize on the adoption of latest technologies in producing biodiesel from used frying oil and microalgae.